Why Care: Complex Evolutionary History of Human Healthcare Networks - Kessler, Sharon E. (Frontiers in Psychology, 2020)
One of the striking features of human social complexity is that we provide care to sick and contagious individuals, rather than avoiding them. Care-giving is a powerful strategy of disease control in human populations today, however, we are not the only species which provides care for the sick. Widespread reports occurring in distantly related species like cetaceans and insects suggests that the building blocks of care for the sick are older than the human lineage itself. This raises the question of what evolutionary processes drive the evolution of such care in animals, including humans. I synthesize data from the literature to evaluate the diversity of care-giving behaviors and conclude that across the animal kingdom there appear to be two distinct types of care-behaviors, both with separate evolutionary histories: 1) social care behaviors benefitting a sick individual by promoting healing and recovery and 2) community health behaviors that control pathogens in the environment and reduce transmission within the population. By synthesizing literature from psychology, anthropology, and biology, I develop a novel hypothesis (Hominin Pathogen Control Hypothesis) to explain how these two distinct sets of behaviors evolved independently then merged in the human lineage. The hypothesis suggests that social care evolved in association with offspring care systems whereas community health behaviors evolved as a type of niche construction. These two types of behaviors merged in humans to produce complex, multi-level healthcare networks in humans. Moreover, each type of care increases selection for the other, generating feedback loops that selected for increasing healthcare behaviors over time. Interestingly, domestication processes may have contributed to both social care and community health aspects of this process.